Experimental discussion on a 6-kW, 2-kWh battery energy storage system using a bidirectional isolated DC/DC converter - Abe T. (2023)
This paper presents an experimental discussion on a 6-kW, full-bridge, zero-voltage switching bidirectional isolated dc/dc converter for a 53.2-V, 2-kWh Li-ion battery energy storage system. The combination of high-frequency switching devices, 600-V/200-A IGBTs and 100-V/500-A MOSFETs with a high-frequency transformer reduces the weight and physical size of the bidirectional isolated dc/dc converter. The dc voltage on the high-voltage side of the converter is controlled in a range of 300V to 355V as the battery voltage on the low-voltage side varies from 50V to 59V. Experimental verification of bidirectional power flow into (battery charging) or out of (battery discharging) the Li-ion battery bank is also presented. The maximal efficiency of the dc/dc converter is measured to be 98.1% during charging and 98.2% during discharging, excluding the gate drive loss and control circuit loss. 2012 The Institute of Electrical Engineers of Japan.